The Evolution of Domestic Abuse as a Process (DAP) Model: An Initial Statement - Burke, Jessica L.; Eargle, Lisa A.; Doucet, Jessica M. (International Journal of Criminology and Sociology, 2024)
A new model of intimate partner violence, the Domestic Abuse Process (DAP) model, is presented to address how domestic abuse emerges, evolves, and escalates in a romantic relationship over time. A review of the relevant literature on intimate partner violence, including studies examining the role of resources, relationship goals and means for achieving these goals, and relationship stressors is conducted. Important theories such as symbolic interactionism, strain, intergenerational transmission of violence, and the process model of family violence are also reviewed and discussed within the context of domestic abuse. A short discussion of how the proposed model could be empirically tested using a survey instrument containing numerous items that are administered to respondent couples is provided. Follow-up interviews with respondent couples would be used to clarify survey responses and to obtain more detailed insights into how abuse entered and intensified in respondent relationships. Both quantitative and qualitative analyses would be performed on the subsequent data to glean important factors and patterns empirically involved in the process. The model provides additional insights into intimate partner violence and abuse that could inform treatment practices and policy.